Types of Crimes Committed and Differences in the Personalities of Their Perpetrators (Archives of Criminology, 2008)
In his article, Stanik discusses the issue of identifying the differences in the personalities of offenders who commit different types of crimes, which would make it possible to understand the motivation behind their actions. In the author’s opinion, it is an indispensable element in the proper execution of the trial, punishment, and effective course of rehabilitation. The text presents research on a group of 129 people convicted of beating, robbery, assault with robbery, and burglary who were beingheld in the semi-open penitentiary in Wojkowice with restrictive and liberalised regimes. The study was conducted using three psychological inventories: the IBZO DSM-IV by Radochoński and Stanik, the SABD by Buss-Durkee, and the SUI by Stanik. A detailed description of each of the above questionnaires is included in the text as an introduction to the analysis of the research findings, which are presented in tables and show the differences between the convicts who committed the above-mentioned crimes. The text also interprets the results. According to the author, perpetrators of theft and burglary are characterised by deeply rooted attitudes of distrust and suspicion and negation of social and legal requirements. For this reason, according to the author, these crimes are not sporadic. The author also refers to the doctoral dissertation of Kucharewicz (Psychologiczna analiza procesów motywacyjnych przestępstw popełnionych przez nieletnich [A psychological analysis of motivational processes in crimes committed by minors]), which reports the results of research carried out on a group of 36 minors. In conclusion, it can be found that in the majority of the respondents criminal behaviour is motivated by personality mechanisms and not by variable situations.